Outline of changes in cortisol and melatonin circadian rhythms in the security guards of shiraz university of medical sciences - Zahra Zamanian; Mansooreh Dehghani; Hassan Hashemi (International Journal of Preventive Medicine, 2013)
Background: According to the literature, a large number of people working in industries and service providing personnel, such as firefighters, physicians, and nurses are shift workers. The spread of shift working in industrial societies and the incidence of the problems resulting from shift working have caused the researchers to conduct studies on this issue. The present study also aimed to investigate melatonin and cortisol circadian rhythms in the security guards of Shiraz University of Medical Sciences, Shiraz, Iran. Methods: The present study was conducted on 20 security guards of Shiraz University of Medical Sciences. In order to collect the study data, blood samples were taken from the study subjects in different times of the day (1, 4, 7, 10, 13, 16, 19, and 22) and cortisol and melatonin levels were determined using the radioimmunoassay and enzyme immunoassay techniques, respectively. Results: The results showed that as the intensity of light increased at night, the plasma cortisol level increased, as well. Besides, no statistically significant difference was found between the plasma cortisol levels in natural light and 4500-lux light. On the other hand, a significant difference was observed between the plasma cortisol levels in natural light and 9000-lux light as well as 4500- and 9000-lux lights. The study findings also showed that as the intensity of light increased at night, the plasma melatonin level decreased. In addition, a statistically significant difference was found between the plasma melatonin levels in natural light and 4500-lux light. Nevertheless, no significant difference was observed between the plasma melatonin levels in the natural light and 9000-lux light as well as 4500- and 9000-lux lights. Conclusions: The present study aimed to investigate the subsequences of shift working in the security guards of Shiraz University of Medical Sciences and showed that occupational exposure to bright light could affect some biological markers, such as melatonin and cortisol secretion.